Media Digital Islami dan Literasi Nilai dalam Dinamika Etika Bermedia Sosial Generasi Z Muslim - sholihat, khodijah amatulloh; Handoko, Handoko; Waahsturi, Waahsturi; Irawan, Wahyudi Saputra; Syahrin, Muhammad Alfi (Educational Research Center, 2026)
The The rapid development of digital media has transformed communication patterns and online behavior among Generation Z, particularly in relation to social media ethics. Islamic digital media has emerged as a medium for da’wah and value education, expected to promote ethical conduct in digital spaces. This study examines the influence of exposure to Islamic digital media and value literacy on the social media ethics of Muslim Generation Z. Using a quantitative survey approach, data were collected from 37 respondents selected through purposive sampling from a population of 41 individuals. The instrument employed a Likert-scale questionnaire, and data were analyzed using multiple linear regression with SPSS. The findings reveal that exposure to Islamic digital media and value literacy simultaneously have a significant effect on social media ethics (F = 7.670; p < 0.05), explaining 31.1% of the variance (R² = 0.311). However, partial analysis shows that only value literacy has a positive and significant effect, while exposure to Islamic digital media is not statistically significant. These results highlight the central role of internalized values in fostering ethical social media behavior among Muslim Generation Z.